Risk management analysis of public street lighting (SMART PJU) as Quick win smart environment of Semarang City - Manggalou, Singgih; Azizatun Nafi’ah, Binti; Uang, Yulinda (International Journal of Science, Technology & Management, 2023)
Successful implementation of a program is the goal of program design. However, currently, many programs fail to be implemented due to the failure of efforts to prevent the occurrence of failure factors. Especially in the era of digital governance such as today, the planning of various smart city programs has a large potential risk of implementation failure. The Semarang City of Smart PJU, for example, the implementation of the use of analytics-based SMART PJU requires long and careful preparation. Not only management preparation but risk management is also needed for the program. This research aims to analyze the map of potential risks in the Semarang City SMART PJU of IoT program along with analyzing how the risk management of the program. This research is based on qualitative research with primary and secondary data collection techniques. Primary data collection by interviewing related informants purposively, then the data is analyzed based on qualitative analysis. The findings of this research are that the highest level of risk occurs in the shortage of human resources and SMART PJU operators because there are no human resources who are data analytic experts and Artificial Intelligence experts. Other high risks are database errors / down; SMART PJU devices using old technology; long loading dashboards; and no Fiber Optic connection in internet management.